DEVELOPMENT OF PRACTICAL AND CREATIVE SKILLS THROUGH THE EGC (ENGINEERING GRAPHIC COURSE) PLATFORM AS AN EXAMPLE OF STUDENTS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS - Madaminov , Javlonbek Zafarjonovich (Educational Research in Universal Sciences, 2023)
This article describes the importance of the EGC (Engineering Graphics Course) platform in developing students’ practical and creative skills in the design process and developing self-directed learning processes. Theoretical and practical results of the role of the EGC (Engineering graphic course) platform in the implementation of the design process are explained when students master it using modern graphics programs such as KOMPAS 3D V20.0.1., AutoCAD, SolidWorks, 3D Max.